2020
DOI: 10.1007/s13300-020-00851-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Acceptance and Commitment Therapy on Pain Acceptance and Pain Perception in Patients with Painful Diabetic Neuropathy: A Randomized Controlled Trial

Abstract: Introduction: Neuropathic pain is a complex phenomenon in patients with diabetes. These patients have many problems, such as psychological problems, high-level pain perception, and pain acceptance. This study aimed to evaluate the effectiveness of acceptance and commitment therapy on pain acceptance and pain perception in patients with painful diabetic neuropathy. Methods: This study was performed according to the clinical trial method. The sample size was 50 participants. In this study, participants were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…Recently, the rst and corresponding author of this paper conducted extensive research in PDN. In our published works for that project, we found that increasing sleep quality and pain acceptance and reducing pain catastrophizing and depression can reduce PDN symptoms and also increase response to treatment and consequently improve Qol in patients with PDN (8,11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the rst and corresponding author of this paper conducted extensive research in PDN. In our published works for that project, we found that increasing sleep quality and pain acceptance and reducing pain catastrophizing and depression can reduce PDN symptoms and also increase response to treatment and consequently improve Qol in patients with PDN (8,11).…”
Section: Discussionmentioning
confidence: 99%
“…The Persian version of the CPAQ also has shown adequate psychometric properties. The assessment of the psychometric properties of the Persian version has shown that the CPAQ had a Cronbach's alpha of 0.89 and test-retest reliability of 0.71 (11).…”
Section: Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acceptance and commitment therapy (ACT) is a psychological modality that has been used with increasing interest in chronic pain. It is considered a third-wave of CBT and can be used alongside more traditional CBT [41][42][43]. Traditional CBT approaches are focused on identifying thoughts, feelings and behaviours that may drive and maintain presenting psychological difficulties.…”
Section: Psychological Treatmentsmentioning
confidence: 99%